Fatores desencadeantes de estresse nos magistrados: o caso de Minas Gerais - Silva, Judite Pereira da (2005)
This work arose due to the author's coexistence with the Judiciary, in the interior of the State of Minas Gerais. It is a descriptive research with documentary analysis, which had the State of Minas Gerais and the State Court of Justice as the places where it was carried out. The population was made up of 930 mining magistrates. The data were collected by officials from the Judiciary Records department, in the archives of the TJMG. A closed questionnaire was used, including questions about: age, marital status, place of work and time off sick leave in the last two years. These data were collected, being tabulated and analyzed using the Windows Excel program. The final conclusions revealed that social changes, technological advances and globalization are factors that contribute to the accumulation of work by judges, which can trigger stress and that mobility, promotions during the career, administrative functions and the first year of exercise professional situations are felt as stressful by the magistrates. The number of days off work, due to sick leave, suggested a high degree of illness in the surveyed population. From these analyzes it is proposed that this research can contribute to the improvement in the organization of the work of the Judges Mineiros, in order to prevent the development of stress in these professionals.